The Mediation Role of Consumer Satisfaction on the Influence of Experiental Marketing and Price Perception on Repeat Purchase Interest at Kopi Klotok Kaliurang Yogyakarta - Dewi, Risma Vimala Surya; Nuvriasari, Audita (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to analyze the mediating role of consumer satisfaction on the influence of experiential marketing and price perception on repurchase interest in Kopi Klotok Kaliurang Yogyakarta. The sample in this research was 100 respondents using a non-probability sampling method with the research instrument used was a questionnaire. The instrument test results stated that the data in this study was proven to be valid and reliable. The results of the AVE value show that the convergent test meets the required criteria. The results of this research prove that: (1) Experiential marketing has a positive and significant effect on repurchase interest at Kopi Klotok Kaliurang Yogyakarta. (2) Price perception has a positive and significant effect on repurchase interest at Kopi Klotok Kaliurang Yogyakarta. (3) Consumer satisfaction has a positive and significant effect on repurchase interest at Kopi Klotok Kaliurang Yogyakarta. (4) Experiential marketing has a positive and significant effect on consumer satisfaction at Kopi Klotok Kaliurang Yogyakarta. (5) Price perception has a positive and significant effect on consumer satisfaction at Kopi Klotok Kaliurang Yogyakarta. (6) Consumer satisfaction is able to positively mediate the influence of experiential marketing on repurchase interest at Kopi Klotok Kaliurang Yogyakarta. (7) Consumer satisfaction is able to mediate price perceptions on repurchase interest at Kopi Klotok Kaliurang Yogyakarta.